2021
DOI: 10.14425/jice.2021.10.2.0704
|View full text |Cite
|
Sign up to set email alerts
|

Investigating student satisfaction in remote online learning settings during covid-19 in indonesia

Abstract: This study was to examine student satisfaction in remote online learning environments during COVID-19 in Indonesia. The participants were 65 undergraduate Informatics students from a private university in Surabaya, Indonesia. Data from Strachota's Student Satisfaction survey responses were examined using quantitative analyses. According to the findings, there was a strong and statistically significant relationship between student satisfaction and interaction. According to predictive models, every type of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
2
13
0
5
Order By: Relevance
“…Trong nghiên cứu của Tsang và cộng sự (2021) cho rằng, tương tác giữa sinh viên và giảng viên là loại tương tác hai chiều; trong đó, giảng viên là người khuyến khích sự tương tác trao đổi của sinh viên, lắng nghe, quan tâm đến sinh viên và phản hồi lại ý kiến của sinh viên, ngược lại sinh viên tương tác với người hướng dẫn bằng cách đặt câu hỏi hoặc trao đổi về các hoạt động của khóa học. Tương tác giữa người học với giảng viên là yếu tố ảnh hưởng tích cực đến sự hài lòng (Ngo & Ngadiman, 2021;Ali & Ahmad, 2021).…”
Section: Giả Thuyết H2: Tương Tác Giữa Sinh Viên Với Sinh Viên Có ảNh...unclassified
See 1 more Smart Citation
“…Trong nghiên cứu của Tsang và cộng sự (2021) cho rằng, tương tác giữa sinh viên và giảng viên là loại tương tác hai chiều; trong đó, giảng viên là người khuyến khích sự tương tác trao đổi của sinh viên, lắng nghe, quan tâm đến sinh viên và phản hồi lại ý kiến của sinh viên, ngược lại sinh viên tương tác với người hướng dẫn bằng cách đặt câu hỏi hoặc trao đổi về các hoạt động của khóa học. Tương tác giữa người học với giảng viên là yếu tố ảnh hưởng tích cực đến sự hài lòng (Ngo & Ngadiman, 2021;Ali & Ahmad, 2021).…”
Section: Giả Thuyết H2: Tương Tác Giữa Sinh Viên Với Sinh Viên Có ảNh...unclassified
“…Tương tác sinh viên với sinh viên là sự tương tác giữa một người học và những người học khác trong một nhóm học tập hoặc trong một lớp học trực tuyến đồng bộ ở thời gian thực có giáo viên hướng dẫn (Moore, 1989). Tương tác giữa người học với người học là yếu tố ảnh hưởng tích cực đến sự hài lòng (Ngo & Ngadiman, 2021). Tuy nhiên, trong nghiên cứu của Gray và DiLoreto (2016) cho rằng, tương tác giữa người cộng sự, 2018).…”
Section: Giả Thuyết H1: Cấu Trúc Khóa Học Có ảNh Hưởng Tích Cực đếN S...unclassified
“…Palloff and Pratt (2001) added a fourth type of interaction that Strachota (2003) labeled learner–technology interaction, referring to learners’ ability and level of comfort in their interactions with online environments (e.g., use of computers, software, and the Internet). Empirical research has shown that these different types of interaction play an important role with regard to achievement outcomes, the experience of meaningful learning, and learner satisfaction ( Driver, 2002 ; Frey and Alman, 2003 ; Strachota, 2003 ; Finlay et al, 2004 ; Chang and Smith, 2008 ; Bernard et al, 2009 ; Abrami et al, 2011 ; Chang, 2013 ; Kuo et al, 2013 ; Alqurashi, 2019 ; Basith et al, 2020 ; Ngo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Learning effectiveness in this study is the ability to achieve the goals that have been set which results in changes in both attitudes and new skills in this case language skills, especially English in students, shown by results in the form of satisfactory scores in the online learning environment during the Covid-19 pandemic. The aspects studied include the quality of the media (Arizona et al, 2020;Salehudin, 2020), the quality of the students (Wilson, 2020), the quality of the modules/materials (Sun, 2016;Wu &Liu, 2013, andBao, 2020), the quality of the learning methods, and the quality of the tutors/trainers (Gray & Diloreto, 2016;Ngo et al, 2021;Suryani & Sugianingrat, 2021). The statistical analysis technique used is the Structural Equation Model (SEM) -PLS/ Partial Least Square with assisted by Smart PLS software.…”
Section: Introductionmentioning
confidence: 99%